Topical Application of a Novel Oxycodone Gel Formulation (Tocopheryl Phosphate Mixture) in a Rat Model of Peripheral Inflammatory Pain Produces Localized Pain Relief Without Significant Systemic Exposure. Issue 7 (20th May 2015) - Smith, Maree T.; Wyse, Bruce D.; Edwards, Stephen R.; El‐Tamimy, Mahmoud; Gaetano, Giacinto; Gavin, Paul
<x xml:space="preserve">Abstract</x> This study was designed to assess the analgesic efficacy and systemic exposure of oxycodone administered topically in a novel tocopheryl phosphate mixture (TPM) gel formulation, to the inflamed hindpaws in a rat model of inflammatory pain. Unilateral hindpaw inflammation was induced in male Sprague–Dawley rats by intraplantar (i.pl.) injection of Freund's complete adjuvant (FCA). Mechanical hyperalgesia and hindpaw inflammation were assessed by measuring paw pressure thresholds and hindpaw volume, respectively, just prior to i.pl. FCA and again 5–6 days later. The analgesic effects of oxycodone administered topically (1 mg in TPM gel) or by i.pl. injection (50 μg), were assessed. Systemic oxycodone exposure was assessed over an 8‐h postdosing interval following topical application. Skin permeation of oxycodone from the gel formulation was assessed in vitro using Franz diffusion cells. Oxycodone administered topically or by i.pl. injection produced significant (p < 0.05) analgesia in the inflamed hindpaws. Systemic oxycodone exposure was insignificant after topical dosing. The in vitro cumulative skin permeation of oxycodone was linearly related to the amount applied. Topical TPM/oxycodone gel formulations have the potential to alleviate moderate to severe inflammatory pain conditions with minimal systemic exposure, thereby avoiding central nervous system (CNS)‐mediated adverse effects associated with oral administration of opioid analgesics. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2388–2396, 2015